Mesenchymal stem cells in tendon repair and regeneration: basic understanding and translational challenges. Issue 1 (5th October 2016) - Leong, Daniel J.; Sun, Hui B.
Abstract : Tendon injuries are common and present a clinical challenge because they often respond poorly to treatment and require prolonged rehabilitation. Current treatments often do not completely repair or regenerate the injured or diseased tendon to its native composition, structure, and mechanical properties. Stem cell–based therapies have brought new hope for tissue repair and regeneration, including that for tendon rupture and tendinopathy. Despite tremendous effort and progress, the success of stem cell–based studies on tendon repair and regeneration has mainly been limited to preclinical studies with few clinical applications. In this concise review, we discuss basic understanding and translational challenges of using mesenchymal stem cells (MSCs) for tendon repair and regeneration, with a focus on (1) tendon stem/progenitor cells (TSPCs) and therapeutic approaches using TSPCs and other MSCs, ( 2) regulation of fate determination in MSCs for tendon‐lineage differentiation, (3) pretreatment and condition of stem/progenitor cells for transplantation, and (4) a treatment approach that involves stimulating endogenous stem cells to enhance tendon healing. The review concludes with discussion on future directions.